"Zasiądzie w pokoju na wieki" (2 Bar 73,1). Pokój jako element mesjańskiej rzeczywistości eschatologicznej w Syryjskiej Apokalipsie Barucha - Miduch, Maria Elżbieta (Verbum Vitae, 2016)
The Second Book of Baruch is a Jewish apocalypse coming from the period right after the destruction of the Temple by Titus in 70 AD. It is the record of theological reflection in the aftermath of this event so traumatic for all Jews. The messiah, his mission and his kingdom all play important roles in this book. The author of the Syriac Book of Baruch hopes for help for all the Israelites through messianic intervention. In his view, the eschatological works of God are equal to the work of messiah. Moreover, in the world of chaos, wars and abuse there is yet hope for true and stable peace. It is much more than just an armistice, rather the depth of peace will be revealed when the messiah comes to rule. His description stands in contrast to the reality in which the Chosen Nation then found itself.